Central Asian Regional Economic Cooperation Program as Driver of Regional Energy Projects to Promote Energy Security in the Post-Soviet Central Asia - F. S. Aminjonov (Проблемы постсоветского пространства, 2019)
The resource-sharing mechanism, which ensured sufficiency and reliability of energy supplies within the Central Asian energy system (CAES) collapsed soon after the disintegration of the Soviet Union. Isolationist energy policies, both in terms of full self-reliance and self-control, without the establishment of self-sustaining independent energy systems, not only threatened security of energy supplies, but also, to a different extent, hampered the socio-economic development in Central Asia. In an attempt to mitigate the negative impact of the new energy policies, the Asian Development Bank (ADB) supported Central Asia Regional Economic Cooperation (CAREC) was introduced as one of the key programs to ensure sustainable access of the population and economies to energy. One of the top priority areas has been strengthening regional cooperative dynamics in the energy sector. Primarily focusing on regional cooperation CAREC attempts to solve the problem of uneven distribution and seasonal variation of energy production in the region, assuming that this would lead to better standards of life and economic growth. This article aims to analyze the extent of contribution of CAREC energy initiatives to improve energy security and promote energy–led economic growth in Central Asia through regional energy projects.